Impact of Animated Video–Based Education on Breast Care Knowledge Among Female University Students at Bale Bandung University - Solihat Holida, Siti; Budiman, Budiman; Nadirawati, Nadirawati; Murtiningsih, Murtiningsih; Safarina, Lina (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Adequate knowledge of breast care is essential for young women to support early prevention of breast health problems, including breast cancer. Effective and engaging nursing health education strategies are needed to improve students' understanding. Objective: This study aimed to examine the effectiveness of Health Promotion Model–based animated video education in improving breast care knowledge among female university students. Method: A quasi-experimental study with a pretest–posttest control group design was conducted among first-year female students at Universitas Bale Bandung. A total of 122 participants were divided into an experimental group (n = 60) and a control group (n = 62). The experimental group received a 13-minute animated educational video, while the control group received no intervention. Knowledge was measured using a validated questionnaire and analyzed using the Wilcoxon test with a significance level of 0.05. Result and Discussion: The experimental group showed a significant increase in mean knowledge scores after the intervention, whereas the control group showed no improvement and tended to experience a decrease. The findings indicate that animated video education effectively enhances students' understanding of breast care. Conclusions: Health education using animated video is effective in increasing breast care knowledge among female university students and can be applied as an alternative nursing strategy in campus-based health promotion programs